(untitled) (Medical Forum Monthly, 2021)
Objective: To assess the levels of blood glucose efficacy of escitalopram on normal male Wistar Rats and assess the efficacy on release of insulin from pancreatic beta - cells in male Albino Mice on dose-based escitalopram. Study Design: An experimental Study Place and Duration of Study: This study was conducted at the Department of Animal Husbandry and Veterinary Sciences at University of Sindh, Tando Jam for a period of six months. Materials and Methods: The rats were randomly assigned to one of five groups: A, B, C, D, or E. On 1st day of the post-experiment period, all animals were sacrificed by cervical dislocation (at end of 5th week). Centrifugation was used to separate serum from clots of blood. SPSS 21.0 was used to analyze data. Significant statistical analysis was characterized as p<0.05. Results: Increasing doses of escitalopram 0.025, 0.05, 0.1, and 0.15 mg/kg/day in groups B, C, D, and E showed progressive reduction in blood glucose levels (p ≤ 0.011). Experimental animals’ groups C, D, and E administered with increasing doses of escitalopram 0.05, 0.1, and 0.15 mg/kg/day respectively showed a rise in body weight also. The control group a showed normal liver architecture. Glycogen staining intensity remained increased in groups of rats fed ad libitum at increasing doses of escitalopram 0.025, 0.05, 0.1, and 0.15 mg/kg/day. Conclusion: Escitalopram lowers blood glucose, increases insulin levels, and increases the content of liver glycogen in the rat model.